AN INVESTGATION OF BURNOUT AND LIFE SATISFACTION IN TERMS OF COPING WITH STRESS IN HEALTH CARE WORKERS - Coşkun ARSLAN (Fırat University, 2019)
The aim of this study was to investigate life satisfaction and burnout in terms of coping with stress in health care workers. The participants were 474 (310 female and 164 male) who participated in the research voluntarily. Data were collected using, Coping with stress scale (Türküm,2002), MAslach Burnout Scale (Maslach & Jackson, 1981) and life satisfaction scale (Diener, Emmons, Larsen & Griffin, 1985). SPSS 18.0 was used in order to evaluate the data which were collected from scales employed in the research. The Pearson correlation coefficient technique was used to determine the relationship between coping with stress, life satisfaction and burnout. Multiple regression analysis was used to search whether coping with stress significantly explain life satisfaction and burnout. As a result of the study, it was found that there was a significant negative relationship between emotional burnout and coping with stress total point, problem- focused coping and avoidance. It was found that there was a significant negative relationship between depersonalization and problem- focused coping and social support. Also It was found that there was a significant positive relationship between personal accomplishment and problem- focused coping, social support and avoidance. Besides, it was found that some approaches of coping with stress significantly explain life satisfaction and approaches of burnout.